Factors associated with hospitalization times and length of stay in patients with bipolar disorder - Shi, Xiaoning; Zhao, Yingying; Yang, Haichen; Xu, Xiufeng; Fang, Yiru; Yu, Xin; Tan, Qingrong; Li, Huichun; Sun, Guangqiang; Wu, Hang; Wang, Pengfei; Yang, Jie; et al. (Frontiers in Psychiatry, 2023)
Aim: Appraise the clinical features and predictive factors of the hospitalization times and length of stay in bipolar disorder (BD) patients. Methods:520 bipolar I and II outpatients in 7 hospitals from 6 cities in China from February 2013 to June 2014 were recruited and followed up using a continuous sampling pattern. The research included a retrospective period of 12 months and the prospective period of 9 months. We collected the demographic and clinical features of the patients. The predictive role of selected variables that could affect the length of stay and hospitalization times were analyzed. Results: Poisson's regression analysis showed that suicide times (IRR=1.20, p<0.001), use of antipsychotic (IRR=0.62, p=0.011), and use of antidepressant (IRR=0.56, p<0.001) predicted more hospitalization times. Linear regression analysis showed that BD type II (β=0.28, p=0.005) and unemployment (β=0.16, p=0.039) were correlated to longer hospitalization length of stay. However, patients who experienced more suicide times (β=-0.21, p=0.007) tended to have a shorter length of stay. Conclusion: Overall, BD patients with more hospitalization times were characterized by higher severity and complex polypharmacy. BD type II, and unemployed patients experienced longer lengths of stay. However, patients with more suicide times tend to have inadequate therapy and poor compliance.